Survey of Nurses\' Viewpoints on Causes of Medicinal Errors and Barriers to Reporting in Pediatric Units in Hospitals of Mashhad University of Medical Sciences - Masoomeh Seidi; Roghih Zardosht (Fasa University of Medical Sciences, 2012)
Background and Objective: Patient safety is the principal concern of current health care delivery systems, and several recent studies initiated by the Institute of Medicine have reported a high incidence of medicinal errors. Of the approximately 44000-98000 patient deaths reported each year because of medical errors, 7000 are attributed to medicinal errors. The purpose of this study was to determine nurses' perceptions of causes of medicinal errors and barriers to reporting them in the pediatric wards of Mashhad University of Medical Sciences. Materials and Methods: This cross-sectional descriptive study recruited156 nurses working in general pediatric units via the convenience sample method. A questionnaire containing four sections was used: the first section on demographic information the second on the reasons for medicinal errors the third on the estimation of the percentage of medicinal errors occurring in the units and the final section on the reasons for failing to report the medicinal errors. Results: The most important medicinal errors from the nurses' viewpoint were failure to check medicinal orders (73.9%) and errors in the medication administration (64%). The nurses estimated that only 45% of all the medicinal errors were reported, and they cited a lack of knowledge about unit policies and routines (59.8%) and negligence to report (59.8%) as the most important reasons for the failure to report the errors. Conclusion: We need to improve the accuracy of medicinal error reporting by nurses and to provide a hospital environment conducive to preventing errors from occurring.